2015
DOI: 10.5812/asjsm.26839
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation of the Micheli Functional Scale to Persian Language for Evaluation of Low Back Pain in the Young Athletes

Abstract: Background:A clinical outcome tool is needed for the assessment of young athletes with low back pain.Objectives:To translate and culturally adapt the Micheli functional scale (MFS), a self-report questionnaire developed to evaluate young athletes with low back pain (LBP) into Persian language and examine the reliability and validity of the Persian MFS (PMFS).Materials and Methods:A cross-sectional study was conducted to assess the psychometric properties of the PMFS. The PMFS was cross-culturally adapted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In this scale, number 10 means severe pain and number 0 means no pain. The validity and reliability of VAS were reported in Breivik et al16 Translation of this scale into Persian language is available and its validity/reliability was well documented 17,18…”
Section: Methodsmentioning
confidence: 94%
“…In this scale, number 10 means severe pain and number 0 means no pain. The validity and reliability of VAS were reported in Breivik et al16 Translation of this scale into Persian language is available and its validity/reliability was well documented 17,18…”
Section: Methodsmentioning
confidence: 94%
“…Of the 60 articles, most were surveyed in athletes in Germany [14,18,49,[52][53][54][55][56][57][58][59][60][61][62], in Sweden [3,[63][64][65][66], and in Iran [36,37,[67][68][69]. Moreover, also in Norway [11,70,71], Poland [72][73][74], United States [50,51,75], the Netherlands [76,77], Belgium [78], Switzerland [12,79], Finland [80,81], Australia [82,83], Spain [84,85], Saudi Arabia [86,87], Estonia [88], Serbia [89], New Zealand [90], Ukraine [91], China…”
Section: Resultsmentioning
confidence: 99%
“…Another review on questionnaires [115] also identified a low number of articles for methodological quality assessment. In this research, these five articles validated the following questionnaires: MFS [36,68], PFRI [37,67], and ADI [22]. Upon evaluating each instrument individually, it was realized that the instruments differed substantially in terms of items and extent to which their psychometric properties were evaluated; thus, each instrument possesses an objective and functionality.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On this scale, number 10 means severe pain and number zero means no pain. The Validity and reliability of instrument VAS are said in Breivik and et al evidences (Breivik et al, 2008).Translation of this scale into Persian language is to be and its validity/reliability is properly documented (Mousavi, Hadian, Abedi, & Montazeri, 2009;Naghdi et al, 2015).…”
Section: Outcome Measuresmentioning
confidence: 99%